جماليّة الدهشة في قصيدة (الهايكو) العربيّة بين الاقتصاد اللّغوي والتّكثيف الدلالي - بواحمال, آمال; بن عافية, وداد (جامعة الوادي - University of Eloued, 2021)
يرى المتتبّع لملامح قصيدة (الهايكو) العربيّة أنّها لا تمنح نفسها في قراءة واحدة؛ كونها زاخرةً بالدهشة والمفاجأة وموسومة بالعمق الفنّي والمعرفي والإبداعي؛ فهي قصائد تتوق الوصول إلى رؤى الآخر وتجسّد طموحاته عبر اللّمحة الدالة والأثر الفاعل. وعليه ارتأت هذه الدراسة أن تقف عند قصيدة (الهايكو) العربيّة، لما تملكه من تداخل التّقنيّات والجماليّات واقتصاد البنية اللّغويّة لتكثّف المعنى وتكتنزه، ممّا يتيح لهذه القصيدة قدرة تأثيريّة مباغتة ومفاجأة جماليّة في تلقّيها، لتخلق قارئا إبداعيّا متطلّعا يتفاعل معها فهمًا واستقراء وتأويلا؛ وذلك من أجل استنطاق وفكّ مغاليق النّص وتفجير دلالته. وقد توصّل البحث إلى عدّ قصائد ا(لهايكو) أشعارا صامتة ومقتصدة لغويّا، في حين فهي حبلى بدلالات متعدّدة وعميقة، تعبق بروائح التّأمّل العميق، تختزن طاقات إيحائيّة تنفجر جمالا عبر القراءة والتّأويل. تتمحور المهمّة الأصيلة لقصيدة (الهايكو) حول إحداث إدهاش المتلقّي، وهي نقلة إبهارية دهشوية تدقّ جرس الإنذار الاستيعابي لديه، ليكون أكثر وعيا في استلهام معانيها المشفّرة، وإحالتها إلى ذاكرته التّفسيرية، ليكون الشريك الفاعل مع المبدع. Whoever follows the features of the Arabic poem, Haiku, sees that it does not give itself in one reading as it is full of amazement and surprise and marked with artistic, cognitive and creative depth; they are poems that yearn to reach the visions of the other and embody his aspirations through a sign of indication and active impact. Accordingly, this study attempts to deal with the Arabic poem of Haiku, because it possesses the intertwining of techniques, aesthetics, and the economy of the linguistic structure to condense and accumulate meaning, which gives this poem a surprising ability and an aesthetic effect in receiving it to create an aspiring creative reader who interacts with it in terms of understanding, extrapolation and interpretation. This is in order to interrogate and decipher the text’s closures and to detonate its connotation and significance. The research has reached many Haiku poems that are silent and linguistically economical poems, while they are pregnant with multiple and deep connotations, filled with the scents of deep contemplation, storing suggestive energies that explode beautifully through reading and interpretation. The original mission of the Haiku poem is centered around causing astonishment to the recipient, and it is a surprising and astonishing move that rings his internal alarm bell, to be more aware in inspiring its coded meanings, and referring it to his interpretive memory to be the active partner with the creator.
مقال
Keywords: الدهشة ; الاقتصاد ; التكثيف ; الدلالة ; الهايكو